What is an Effective Audit, and How Can You Tell? - Bender, Ruth (Cranfield University, 2006)
The Combined Code requires that audit committees conduct an annual evaluation of the effectiveness of the audit process. In order for this to be done properly, committees need to determine what they mean by effectiveness, and to implement appropriate procedures for the evaluation. Audit effectiveness means different things to different people. Formal definitions revolve around the quality, competence, procedures and independence of the audit firm. In practice, the effective audit is less easy to identify than the ineffective audit. However, the latter may only come to light if problems surface at some future time. If there are no underlying problems, the fact that an audit was ineffective may not be apparent. The output of an audit is in the form of a series of reports and presentations. To some extent, the effectiveness of the audit is judged on these, and on the level of service given by the audit firm. The outcome of an effective audit includes financial statements that present a true and fair view, and advice on how the company's processes may be improved. An effective audit is completed to schedule, and with minimal disruption to the company. Prerequisites for an effective audit are an effective audit firm and team. The firm needs sound procedures; the team needs an understanding of the company and industry, together with judgement, objectivity and independence of mind. Some audit committees use checklists as a means to evaluate the effectiveness of their audits. Others choose to do the evaluation in a less formal way, by means of a discussion. In either case, the input of management is essential to the process, as the audit committee members are at a remove from the detail of the audit process. Increased regulation over the past few years has led to pressure on auditors. There is some fear that too much time is being spent on boilerplate and audit checklists, in order to meet review requirements. Audit working papers have improved, but not necessarily audit effectiveness. There is a commercial requirement for auditors to keep fees down, by working more efficiently. However, this must not lead to the audits being less effective.
Keywords: No copyright statement on report. Permission to archive received from Lucy Findlay, Chief of Staff, CBI - Annette - 12/7/11